2011
DOI: 10.1371/journal.pone.0025285
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Enrichment Modulates Cortico-Cortical Interactions in the Mouse

Abstract: Environmental enrichment (EE) is an experimental protocol based on a complex sensorimotor stimulation that dramatically affects brain development. While it is widely believed that the effects of EE result from the unique combination of different sensory and motor stimuli, it is not known whether and how cortico-cortical interactions are shaped by EE. Since the primary visual cortex (V1) is one of the best characterized targets of EE, we looked for direct cortico-cortical projections impinging on V1, and we ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…First we investigated c-Fos expression in MEnt and in pPta, and we found that activation at 1 day in both areas was similar in EE mice, SC mice, and did not differ from that in their home-cage controls (two-way ANOVA, post hoc analysis Holm-Sidak method, all P values > 0.05); however, in the other probe tests performed, significant differences between EE and SC mice and between EE and HC-EE mice were found (see Figure 4 for details). Then, we observed c-Fos expression in V1 and M2, for they are connected to the dorsal stream and there is a direct monosynaptic connection between motor and visual cortices [65]. We found that EE group was statistically different from SC and HC-EE groups in M2, only in probe test performed at 20, 30, and 50 days; instead, in V1, we did not find any difference between EE and SC group, only an increase in c-Fos expression for the late retention delays in both groups (see Figure 5 for details).…”
Section: Resultsmentioning
confidence: 99%
“…First we investigated c-Fos expression in MEnt and in pPta, and we found that activation at 1 day in both areas was similar in EE mice, SC mice, and did not differ from that in their home-cage controls (two-way ANOVA, post hoc analysis Holm-Sidak method, all P values > 0.05); however, in the other probe tests performed, significant differences between EE and SC mice and between EE and HC-EE mice were found (see Figure 4 for details). Then, we observed c-Fos expression in V1 and M2, for they are connected to the dorsal stream and there is a direct monosynaptic connection between motor and visual cortices [65]. We found that EE group was statistically different from SC and HC-EE groups in M2, only in probe test performed at 20, 30, and 50 days; instead, in V1, we did not find any difference between EE and SC group, only an increase in c-Fos expression for the late retention delays in both groups (see Figure 5 for details).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study using simultaneous recordings of local field potentials in awake, freely moving mice and quantifying the degree of linear and nonlinear correlation between the local field potentials in the two regions as a measure of synchronization might offer an explanation (49). It was shown that EE rearing decreased the level of coupling between the electrical activities of the secondary motor cortex and V1 compared with SC mice.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies showed that enrichment improved brain cholinesterase activity [70] and increased cerebral cortex thickness, neuron and glial cell numbers [1, 34]. Subsequent studies have shown that enrichment increases synapses and dendrite complexity [23, 52], neurophysiological synaptic plasticity, cortico-cortical interactions and various molecular mechanisms of synaptic neurotransmission [36, 40, 60, 64, 90], increase neurogenesis and brain neurotrophic factors such as brain-derived neurotrophic factors [63, 104, 137], and alter the brain’s transcriptome [97], proteome [83], and lipidome [106]. A major limitation in interpreting the results of these studies is that it is difficult to distinguish the beneficial effects of physical exercise in an enriched environment from those due to the cognitive or social simulation.…”
Section: Life Experiences and Animal Modelsmentioning
confidence: 99%